Pelaksanaan pembelajaran keterampilan vokasional bagi siswa autis di masa Pandemi Covid-19 - Alfiyati, Ulfa (Piramida Akademi, 2023)
Abstract: The research describes the implementation of vocational learning to make salted eggs: (1) observing other programs and environmental collaboration, (2) adapting the program to the basic competencies of other subjects, (3) involving students in program planning, (4) linking the program with real-world experiences, (5) adapting pre-vocational materials to the real world, (6) research-based vocational learning methods, (7) integrating programs with the school community, and (8) real-world authentic strengthening during school visit activities at Autisma Dian Amanah Yogyakarta SLB during the COVID pandemic -19. This research uses a qualitative case study approach. The research subjects were one vocational supervisor for making salted eggs and two autistic students who took part in the program. Data collection includes interviews, observation, and documentation. Data analysis techniques by condensing and presenting data, as well as drawing conclusions. The results showed: (1) the determination of the program was carried out only through collaboration between parties inside and outside the school, observation was not yet possible, (2) the program was adjusted to the basic competencies of other subjects, (3) the choices, interests and strengths of students were involved in planning, ( 4) teaching academic skills; functional writing, reading, and arithmetic are not yet consistent, teaching vocational skills; money management has not been carried out because of students' abilities, vocational communication has been carried out, decision-making abilities have not been fully carried out, and performance in routine work functions related to making salted eggs has been carried out, (5) teaching of filling out forms and job interviews has not been carried out, (6) research-based learning methods in the form of teacher's past experience and application of methods from year to year, (7) the program is integrated with teachers, principals, administrative staff, parents, and other students, and (8) real-world authentic reinforcement through social reinforcement, food or drink, and other objects or activities. Abstrak: Penelitian mendeskripsikan pelaksanaan pembelajaran vokasional pembuatan telur asin: (1) observasi program lain dan kolaborasi lingkungan, (2) penyesuaian program dengan kompetensi dasar mata pelajaran lain, (3) pelibatan siswa dalam perencanaan program, (4) penghubungan program dengan pengalaman dunia nyata, (5) penyesuaian materi pravokasional dengan dunia nyata, (6) metode pembelajaran vokasional berbasis penelitian, (7) pengintegrasian program dengan komunitas sekolah, dan (8) penguatan autentik dunia nyata saat aktivitas kunjung sekolah di SLB Autisma Dian Amanah Yogyakarta pada masa pandemi COVID-19. Penelitian menggunakan pendekatan kualitatif studi kasus. Subjek penelitian adalah satu pembimbing vokasional pembuatan telur asin beserta dua siswa autis yang mengikuti program. Pengumpulan data meliputi wawancara, observasi, dan dokumentasi. Teknik analisis data dengan kondensasi dan penyajian data, serta penarikan kesimpulan. Hasil penelitian menunjukkan: (1) penentuan program dilakukan hanya melalui kolaborasi pihak dalam dan luar sekolah, observasi belum memungkinkan, (2) program disesuaikan dengan kompetensi dasar mata pelajaran lain, (3) pilihan, minat, dan kekuatan siswa dilibatkan dalam perencanaan, (4) pengajaran keterampilan akademik; menulis, membaca, dan berhitung fungsional belum konsisten, pengajaran keterampilan vokasional; pengelolaan uang belum dilakukan karena kemampuan siswa, komunikasi vokasional dilakukan, kemampuan memutuskan belum sepenuhnya dilakukan, dan kinerja dalam fungsi pekerjaan rutin terkait pembuatan telur asin dilakukan, (5) pengajaran pengisian formulir dan wawancara pekerjaan belum dilakukan, (6) metode pembelajaran berdasarkan penelitian berupa pengalaman masa lalu guru dan penerapan metode dari tahun ke tahun, (7) program diintegrasikan dengan guru, kepala sekolah, staf tata usaha, orang tua, dan siswa lain, dan (8) penguatan autentik dunia nyata melalui penguatan sosial, makanan atau minuman, dan benda atau aktivitas lain.